Evaluation of the stability of salty concentrated yoghurt added with oregano during storage (Research, Society and Development, 2020)
Currently, there is a great demand for products that bring health benefits, with different flavors and above all, safe for consumption. Thus, the objective of this work was to evaluate the physical, physicochemical and microbiological stability of salty concentrated yogurts with and without the addition of oregano during storage and to verify the stability of the total phenolics and antioxidant activity of salty concentrated yogurt added with oregano during storage. Analysis of syneresis, ash, moisture, lipids, proteins, acidity, pH, total count of lactic acid bacteria, total and thermotolerant coliforms, molds and yeasts, total phenolic compounds and antioxidant activity (ABTS and DPPH) were performed. It was observed that the physical aspects (syneresis) and some physicochemical parameters of concentrated salty yogurts were influenced by the addition of oregano, and that both (with and without the addition of oregano) changed during storage. Despite being within the values required by legislation, this study demonstrated that the addition of oregano negatively influences the survival of lactic acid bacteria, inhibiting them, during the cold storage of yogurt. Concentrated salted yogurts with and without oregano added coliform counts within the standards established by Brazilian legislation. Regarding the enumeration of mold and yeasts, this was found outside the standards established by legislation since the beginning of storage. Salty concentrated yogurts added with oregano showed an increase in the content of bioactive compounds during storage, being an interesting alternative for the dairy products market. However, further studies would be needed to decrease the molds and yeast count to the limit permitted by law.